Responses of shallot to ameliorant and actinobacteria applications in water-saturated system on tidal land - Haitami, A.; Ghulamahdi, Munif; Sopandie, Didy; Susila, Anas Dinurrohman; Lestari, Yulin (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2024)
Tidal areas are believed as future land for many commodities in Indonesia. Here, shallot growing was evaluated on tidal land supplemented with soil conditioners. The research aimed to evaluate the adaptive response of shallot varieties for growing on tidal land with a water-saturated system indicating Fe and Al stress by applying soil ameliorant and actinobacterial. The study used a completely randomized factorial design with three replications. The first factor was shallot variety (Bima Brebes, Batu Ijo, and SS Sakato) and the second factor was soil conditioners (no ameliorant, actinobacteria, ameliorant+actinobacteria, and actinobacteria+ameliorant+dolomite). Bima Brebes and Batu Ijo cultivars had the highest growth percentage, age at shoot emergence, plant height, and number of leaves, while the SS Sakato variety had the slowest growth. Shallot production variable had a significant interaction with soil conditioners. Bima Brebes variety demonstrated high suitability for a water-saturated system in tidal land, and actinobacteria+ameliorant+dolomite was a more promising conditioner than other treatments. Keywords: pyrite, saturated soil culture, tidal swamps, growth, yield, marginal land.